A CASE STUDY ON AUTOMATION IN PCP ACTIVITIES WITH SAP AND VBA SCRIPTS - Degrandi, Larissa Aparecida; Caracini, Luiz Gustavo (Revista Interface Tecnológica, 2023)
The objective of this study is to illustrate the benefits of automating repetitive daily activities of ERP systems, reducing manual operations of medium complexity and high execution time, improving operational efficiency by providing real-time information for decision making. To achieve this objective, automations were planned and developed using Visual Basic (VBA) and SAP Scripts, using Microsoft Excel as a platform. Excel’s "affinity" with SAP proves to be very effective, enabling the execution of mass repetitive tasks with greater informational reliability, all without requiring any kind of investment. The study was carried out in the production planning and control department (PCP) in a medium-sized Brazilian company in the metalworking sector, which has 70% of its production of non-series products, thus requiring a strict daily control of inventory and manufacturing management, thus avoiding wasting resources with obsolete inventories.